EVALUASI PROGRAM PENDIDIKAN KESEHATAN MASYARAKAT MODEL STAKE DI DESA PENGLIPUURAN KUBU BALI - Ribek, Nyoman; Susy N.AI, Putu; Mertha, Made (International Journal of Natural Science and Engineering, 2017)
Research aims to investigate the implementation of health education programs to improve community health status Penglipuran Bangli regency. This research is descriptive qualitative research in the form of program evaluation with a design evaluation model programs stake, s. Non probability sampling with purposive sampling. with a sample of 12 informants, health education receiver 5 and 70 filler questionnaires. The data collected by in-depth interviews, documentation, observation and angket. Data analyzed with logical, empirical, and consideration of the suitability of the results. The study concluded there Relevance sufficient to describe the consistency of goals, policies, and services, to meet the needs of the community health education, Still efektip level of achievement of targets, and standard operating procedures were implemented in health education programs, is quite efficient in seeing a comparison between the output with input, Impact positively influence the implementation of health education on health behaviors.Â